Securing the Digital Backbone: Strategies for Resilient Network Security - Rahul Singh Chowhan; Dr. Poonam Keshwani (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
As the internet becomes a basic utility available over all the nooks and corners, binding and sharing the most confidential information on the web has become paramount and hence securing the digital backbones of any and every organization. While connectivity provides unprecedented convenience and efficiency, it also exposes our networks to a host of security issues, such as data breaches, malware attacks, insider risks, and supply chain weaknesses. Firewalls are indispensable gatekeepers that can filter incoming and outgoing traffic based on predefined rules, but they can face difficulties in maintaining complex rule management as well as performance with security. Intrusion detection systems (IDS) (devices that monitor network traffic for patterns indicating suspicious activities) like false positives, evasion methods etc must be addressed as well as traffic be encrypted. Encryption, on one hand, is a fundamental operation to guarantee the confidentiality of sensitive data, but in the meantime, it poses significant challenges in terms of key management and post-quantum readiness. And what about preventative defence methods for cyber attacks and malware like APTs or ransomware, which this paper also examines? We cannot be reminded often enough of the necessity of vigilance, threat intelligence and well-planned incident response.